1985
DOI: 10.1111/j.1471-0528.1985.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytoplasmic steroid receptors and tumour differentiation and invasion in endometrial carcinoma

Abstract: The incidence and levels of cytoplasmic steroid receptors were studied in 155 endometrial carcinomas: oestrogen receptors (ER) were measured in all samples. progesterone receptors (PR) in 148 and androgen receptors (AR) in 1 18. Well-differentiated adenocarcinomas were significantly more likely to contain ER, PR and AR than were poorlydifferentiated tumours, and mean values of ER and PR content were significantly higher in well-differentiated adenocarcinomas than in lessdifferentiated tumours. Receptor profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Diminution of the 20 investigated fibroids showed a great variation, although E2 and P values were continuously and significantly suppressed to the postmenopausal range in all patients. This is in agreement with mor differentiation have been made by Quinn et al (21), who found that poorly differentiated endometrial adeno-and adenosquamous carcinomas are significantly more likely to be ER negative and PgR positive than comparable well differentiated neoplasms.…”
Section: Discussionsupporting
confidence: 92%
“…Diminution of the 20 investigated fibroids showed a great variation, although E2 and P values were continuously and significantly suppressed to the postmenopausal range in all patients. This is in agreement with mor differentiation have been made by Quinn et al (21), who found that poorly differentiated endometrial adeno-and adenosquamous carcinomas are significantly more likely to be ER negative and PgR positive than comparable well differentiated neoplasms.…”
Section: Discussionsupporting
confidence: 92%
“…In clear cell carcinoma, low incidences of ER andlor PR (Creasman et al 1985, Ehrlich et al 1988) and lower mean contents of both receptors yVyholm et al 1992/ZZ) have been found when compared to endometrioid adenocarcinoma. Similarly, in "adenosquamous" carcinoma, lower incidences and mean levels of one or both receptors than found in regular adenocarcinoma have been shown in four studies (Liao et al 1986, Chambers et al 1988, Ehrlich et al 1988, Nyholm et al 1992, while two studies reported receptor levels resembling those of adenocarcinoma (Creasman et al 1985, Quinn et al 1985a. In papillary serous carcinoma low receptor content has also been reported compared to adenocarcinoma (Creasman et al 1985, Chambers et al 1988).…”
Section: Receptor Correlations With Histologic Tumor Typementioning
confidence: 72%
“…1992/Il). Three of these studies reported a relationship between mean tumor receptor levels and invasion (Kauppila et al 1982a, Quinn et al 1985a, Chambers et al 1988).…”
Section: Receptor Correlations With Myometrial Invasionmentioning
confidence: 99%
See 1 more Smart Citation